CURRENT TRENDS IN UKRAINE’S SCIENTIFIC AND INNOVATIVE ACTIVITIES - Mykytiuk , N.Ye. (The actual problems of regional economy development, 2022)
The purpose of this article is to study current trends in Ukraine’s scientific and innovative activity. In the course of the research the methods of analysis and synthesis, theoretical generalization and system approach were used. It is noted that the key condition for ensuring the competitive advantage of economic entities is the ability to produce, implement and capitalize innovations, and the effectiveness of innovative activities of enterprises is mainly influenced by factors related to scientific and scientific-technical work. It is established that in 2020 in Ukraine some components of scientific and innovative activity of enterprises, institutions and organizations intensified, as evidenced by the increase in organizations engaged in research in the public sector and higher education, increase in candidates and doctors of science, increase in researchers, increase in fundamental and applied research costs, increase in innovatively active industrial enterprises, increase in sold innovative industrial products volume. At the same time, the number of organizations and the total number of employees engaged in R&D decreased, as well as the total amount of R&D expenditures and scientific and technical development expenditures, and the share of sold innovative products in total industrial sales. The reasons of scientific and innovative activity negative tendencies in Ukraine are singled out, among which: insufficient state’s financing of the scientific and technical sphere; the crisis caused by the COVID-19 pandemic; enterprises’ support of obsolete production lines, lack of interest of business representatives in cooperation with scientific institutions, as well as their unwillingness to invest in long-term scientific and technical development projects due to high risks of non-return of invested funds; monopolization of the economy and low level of competition. Emphasis is placed on the fact that the active development of Ukraine's economy is possible through the transition to the production of intellectual products, as well as by increasing the share of high-tech industries in the structure of GDP. Measures are proposed, the implementation of which will increase the use efficiency of scientific potential in innovative enterprises. Key words: , , ,